Establish the following formula by principle of mathematical induction.
1(1!)+ 2(2!)+ 3(3!)+............................+n(n!) = (n+1)! - 1
Answers
Answer:
Suppose the statement is true for some value of n (this assumption is the "inductive hypothesis").
We need to show that then the statement is also true for the next value, that is, for n+1. In other words, we need to show that
1(1!) + 2(2!) + 3(3!) + ... + (n+1)(n+1)! = (n+2)! - 1
Starting with the left hand side, we get
1(1!) + 2(2!) + 3(3!) + ... + n(n!) + (n+1)(n+1)!
= (n+1)! - 1 + (n+1)(n+1)! [ by the inductive hypothesis ]
= ( 1 + (n+1) )(n+1)! - 1
= (n+2)(n+1)! - 1
= (n+2)! - 1
So, under the assumption that the statement holds for some value n, the statement then also holds for the next value n+1.
All that remains is to show that the statement is true for some starting value to kick off the whole induction. Checking the statement for n=1, we see
1(1!) = 1×1 = 1 = 2 - 1 = 2! - 1 = (1+1)! = 1.
So the statement holds for n=1, and so by induction, it holds for all natural numbers n.
Hope that helps.